Gastric duplication cysts as a differential diagnosis of gastrointestinal stromal tumor (GIST). Case report; Quistes de duplicación gástrico como diagnóstico diferencial de tumor del estroma gastrointestinal (GIST). Reporte de caso - Gonzalez-Palacios, L (Sociedad de Cirujanos de Chile, 2026)
Objective: To describe the clinical, imaging, and surgical findings of a patient who underwent partial gastrectomy due to suspected GIST, biopsy revealed the presence of three gastric duplication cysts. Materials and Methods: Clinical data were obtained from the patient’s medical record, and a literature review was conducted using the terms “gastric duplication cyst in adults” and “gastric duplication.” Artificial intelligence was utilized for grammatical correction, writing, and modification of some images. Results: A case is presented of a 25-year-old female patient who consulted for nonspecific abdominal symptoms. An imaging and endoscopic study suggested GIST, leading to surgical resolution. Through laparoscopic approach, three gastric lesions were identified: two evident from preoperative imaging and another from intraoperative endoscopy. Resection of these lesions was performed using different techniques, and the patient evolved without incidents. Biopsy confirmed the diagnosis of three gastric duplication cysts. Discussion: Gastric duplication cysts correspond to a rare congenital pathology, with diagnosis predominantly occurring in neonates or pediatric age, being rare in adults. © 2026, Sociedad de Cirujanos de Chile. All rights reserved.